Стан та інституціональне забезпечення системи кредитування аграрних підприємств України в умовах інклюзивної економіки - Степаненко, С. В.; Власенко, Т. А. (My University, 2022)
У статті розкрито аналітичні аспекти системи кредитування і страхування сільськогосподарських підприємств та розробки пропозицій щодо розвитку їх інституціонального забезпечення в Україні. Розглянуто тенденції розвитку банківського кредитування у фінансовому забезпеченні сільськогосподарських підприємств в Україні у період 2015–2022 рр. Проведено оцінку середньої вартості кредитів за комерційними банками України та обсягів кредитування сільськогосподарських підприємств. Визначено динаміку обсягів пільгового кредитування суб’єктів агробізнесу. Встановлено недоліки системи інституційної підтримки фінансово-кредитного забезпечення вітчизняного аграрного бізнесу, серед яких відсутність рівних можливостей доступу до ринку кредитних ресурсів; зростання вартості кредитних ресурсів; відсутність ефективного організаційно-економічного іпотечного кредитування; неврегульованість та тривалість процедур оформлення фінансового лізингу; недосконалий механізм страхування кредитних ризиків позичальників; низький рівень цифровізації сервісу страхових послуг. Обґрунтовано перспективні напрямами удосконалення фінансово-кредитних відносин, якими є: фінансування ланцюгу створення аграрно-продуктової вартості; інноваційний кредитно-аграрний скоринг; створення та функціонування цифрових кредитних платформ. Встановлено, що перспективним напрямом залучення до аграрного бізнесу тимчасово вільних фінансових потоків постають фінансово-технічні стартапи, які працюють на цифрових засадах, передбачають вільний доступ до кредитних ресурсів та швидку автоматизовану оцінку кредитної історії позичальника. The article discloses the analytical aspects of the crediting and insurance system of agricultural enterprises and the development of proposals for the development of their institutional support in Ukraine. It was determined that credit and financial support under modern conditions plays the most important role in ensuring the development of agrarian business. Credit, as the main financial instrument, forms the prerequisites for business capitalization, stimulates the productivity of agricultural production and is reflected in its ability to implement technical and technological changes and ensure the production of competitive products. The loan can act as an effective tool for increasing the level of technical and technological development, implementation of innovative and technological programs and projects. The trends in the development of bank lending in the financial support of agricultural enterprises in Ukraine in 2015–2022 were considered. The average cost of loans from commercial banks of Ukraine and the volume of lending to agricultural enterprises were evaluated. The dynamics of the volume of concessional lending to agribusiness entities was determined. The shortcomings of the system of institutional support for financial and credit provision of domestic agrarian business have been identified, including the lack of equal access to the market of credit resources; increase in the value of credit resources; lack of effective organizational and economic mortgage lending; unsettledness and length of financial leasing registration procedures; an imperfect mechanism for insurance of borrowers' credit risks; low level of digitalization of insurance services. Prospective directions for improvement of financial and credit relations are substantiated, which are: financing of the chain of creation of agricultural and product value; innovative credit and agricultural scoring; creation and operation of digital credit platforms. It has been established that financial and technical startups that work on a digital basis, provide free access to credit resources and a quick automated assessment of the borrower's credit history appear as a promising direction for attracting temporarily free financial flows to agrarian business.
Status and institutional security of the lending system of agricultural enterprises of Ukraine in the conditions of an inclusive economy
Keywords: кредит; банк; сільське господарство; сільськогосподарські підприємства; фінансове забезпечення; лізинг; credit; bank; agriculture; agricultural enterprises; financial support; leasing